1994
DOI: 10.1111/j.1476-5381.1994.tb16999.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential inhibition of neuronal calcium entry and [3H]‐D‐aspartate release by the quaternary derivatives of verapamil and emopamil

Abstract: 1 Verapamil and emopamil are structurally related phenylalkylamine calcium channel/5-HT2 receptor antagonists that differ in their anti-ischaemic properties in experimental studies. The quaternary ammonium derivatives of these compounds were prepared and tested in assays of neuronal voltagesensitive calcium channel (VSCC) function to determine whether the compounds act at intra-or extracellular sites. 2 The compounds were tested in K+-evoked: (1) rat brain synaptosomal 45Ca2+ influx, (2) IntroductionEmopamil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…It has been suggested that the binding site of verapamil on other potassium channels located intracellularly (Cohen et al, 1987;Rauer and Grissmer, 1999) and that their adhesion causes a collapse of the pore (Baba et al, 2015). However, it is also described that verapamil might exert its blockade by interacting with the extracellular side of these channels (Keith et al, 1994). Our dose-responses curves of verapamil with both the membrane depolarization and I RIL report a Hill coefficient that suggest that this effect happens through a similar mechanism which might require at least two interaction sites acting cooperatively in the channel (Monod et al, 1965;Weiss, 1997).…”
Section: Verapamil Induces a Dose-dependent Inhibition Of Trek Currentsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the binding site of verapamil on other potassium channels located intracellularly (Cohen et al, 1987;Rauer and Grissmer, 1999) and that their adhesion causes a collapse of the pore (Baba et al, 2015). However, it is also described that verapamil might exert its blockade by interacting with the extracellular side of these channels (Keith et al, 1994). Our dose-responses curves of verapamil with both the membrane depolarization and I RIL report a Hill coefficient that suggest that this effect happens through a similar mechanism which might require at least two interaction sites acting cooperatively in the channel (Monod et al, 1965;Weiss, 1997).…”
Section: Verapamil Induces a Dose-dependent Inhibition Of Trek Currentsmentioning
confidence: 99%
“…This is the case for class IV antiarrhythmic drugs used in pathological conditions such as chronic angina pectoris, cardiac arrhythmias or hypertension (Kato et al, 2004). In fact, the phenylalkylamine verapamil exerts its therapeutic action predominantly on cardiac cells, reducing heart contractility and rate (Cohen et al, 1987), by blocking L-type calcium channels (Keith et al, 1994;Bergson et al, 2011). Notwithstanding, verapamil has also been shown to exert a significant inhibition of T-type calcium channels expressed in both native and heterologous systems (Freeze et al, 2006;Bergson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hanatoxinas, encontradas na peçonha de G. spatulata inibem canais de potássio do tipo Kv2.1 e Kv4.2 [56], enquanto a omega-grammotoxin SIA (GsTxSIA) bloqueia os canais de cálcio dependentes de voltagem do tipo N, P e Q [47,57].…”
Section: Ação Em Canais Iônicosunclassified